Income inequality within smallholder irrigation schemes in Sub-Saharan Africa - Manero, Ana (Informa UK Limited, 2017)
Equitable income distribution is recognized as critical for poverty reduction, particularly in developing areas. Most of the existing literature is based on region- or country-wide data; fewer empirical studies exist at community levels. This article examines income disparities within six smallholder irrigation schemes in Zimbabwe, Tanzania and Mozambique, comparing inequality at local and national levels, as well as decomposing inequality by group and by source. The results present significant contrasts between schemes and compared to national figures. This evidences that, inadvertently, nation-wide strategies may overlook high inequality at smaller scales, and thus, development policies should be tailored to the specific areas of intervention.